Neo-Institutional Theory and Organization Studies: A Mid-Life Crisis? - Alvesson, Mats; Spicer, André (Organization studies, 2019)
We trace the development of neo-institutional theory in Organization Studies from a marginal topic to the dominant theory. We show how it has evolved from infancy, through adolescence and early adulthood to being a fully mature theory, which we think is now facing a mid-life crisis. Some of the features of this mid-life crisis include over-reach, myopia, tautology, pseudo-progress and re-inventing the wheel. To address these problems, we argue that institutional theorists should limit the range of the concept, sharpen their lens, avoid tautologies and problematize the concept. By doing this, we think institutional theorists could develop a narrower and more focused conception of institutions.